Impact of DNA extraction and sampling methods on bacterial communities monitored by 16S rDNA metabarcoding in cold-smoked salmon and processing plant surfaces. (May 2021) - Maillet, Aurélien; Bouju-Albert, Agnès; Roblin, Steven; Vaissié, Pauline; Leuillet, Sébastien; Dousset, Xavier; Jaffrès, Emmanuel; Combrisson, Jérôme; Prévost, Hervé
Abstract: Amplicon sequencing approaches have been widely used in food bacterial ecology. However, choices regarding the methodology can bias results. In this study, bacterial communities associated with cold-smoked salmon products and their processing plant surfaces were monitored via sequencing of the V3–V4 region of the 16S rRNA gene. The impact of DNA extraction protocols, sampling methods (swabbing or sponging) and surface materials on bacterial communities were investigated. α and β diversity analyses revealed that DNA extraction methods mainly influence the observed cold-smoked salmon microbiota composition. Moreover, different DNA extraction methods revealed significant differences in observed community richness and evenness. β- Proteobacteria: Photobacterium, Serratia and Firmicutes : Brochothrix, Carnobacterium and Staphylococcus were identified as the dominant genera. Surface microbiota richness, diversity and composition were mainly affected by cleaning and disinfection procedures but not by DNA extraction methods. Surface community richness and evenness appeared higher when sampled by sponging compared to swabbing. β-diversity analyses highlighted that surface topology, cleaning and disinfection and sampling devices seemed to affect the bacterial community composition. The dominant surface bacteria identified were mainly Flavobacteriaceae, β- Proteobacteria and γ- Proteobacteria described as fish spoilers such as Acinetobacter, Pseudomonas and Shewanella . DNA extraction and sampling methods can have an impact on sequencing results and the ecological analysis of bacterial community structures. This study confirmed the importance of methodology standardization and the need for analytical validation before 16S rDNA metabarcoding surveys. Highlights: The DNA extraction methods choice impacts the observed richness of cold-smoked salmon bacterial communities. Surface microbiota diversity was mainly affected by cleaning and disinfection procedure but not by the DNA extraction methods. Methodology harmonization should be considered for 16S rDNA metabarcoding studies.